2012
DOI: 10.3892/ol.2012.905
|View full text |Cite
|
Sign up to set email alerts
|

8-Chloroadenosine 3′,5′-monophosphate induces cell cycle arrest and apoptosis in multiple myeloma cells through multiple mechanisms

Abstract: Abstract. The aim of this study was to investigate the molecular mechanism of 8-chloroadenosine 3',5 in the inhibition of the growth and induction of apoptosis of multiple myeloma (MM) cells. Two MM-derived cell lines, RPMI-8226 and U266, were used. Cell viability, apoptosis induction and mitochondrial transmembrane potential were determined and the expression levels of cell cycle regulatory proteins (Cdk2, cyclin E, p27 and c-myc) and p38 mitogen-activated protein kinase (MAPK) protein were detected. Followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Daniel PM et al proposed that the pharmacological activation of cAMP in glioblastoma (GBM) cells led to the increase of proapoptotic BIM (Bcl-2 interacting mediator of cell death) expression and apoptosis in specific types of GBM cells 17 . Cheng YM et al and Follin-Arbelet V et al showed that cAMP could induce apoptosis in multiple myeloma cells in vitro 43 , 44 . However, Hara M et al showed that vasoactive intestinal peptide could prevent the progression of hepatocellular carcinoma (HCC) by increasing apoptosis through inhibiting cAMP / Bcl-xL pathway 45 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Daniel PM et al proposed that the pharmacological activation of cAMP in glioblastoma (GBM) cells led to the increase of proapoptotic BIM (Bcl-2 interacting mediator of cell death) expression and apoptosis in specific types of GBM cells 17 . Cheng YM et al and Follin-Arbelet V et al showed that cAMP could induce apoptosis in multiple myeloma cells in vitro 43 , 44 . However, Hara M et al showed that vasoactive intestinal peptide could prevent the progression of hepatocellular carcinoma (HCC) by increasing apoptosis through inhibiting cAMP / Bcl-xL pathway 45 .…”
Section: Resultsmentioning
confidence: 99%
“…According to the above results, several frontiers and hotspots of research focus on cAMP signaling system in cancer field were extracted as follows: cAMP signaling pathway is related to cancer cell apoptosis Generally, cAMP signaling pathway was confirmed to be inhibited in many reported cancer tissues [17]. A lot of studies have shown that if the cAMP level in cancer tissue is enhanced, the apoptosis of tumor cells can be promoted, thus inhibiting tumor growth [42,43,44]. Abudoureyimu A et al found that As2O3 induced gastric cancer BGC-823 cell apoptosis by up regulating cAMP level and down regulating PKC level [42].…”
Section: Research Frontiers and Hotspotsmentioning
confidence: 99%